Effects of human resource management practices on organizational performance : an empirical study of oil and gas industry in Malaysia / Yashar Shams, Leila Radmand and Yasser Batoie - Radmand, Leila; Batoie, Yasser; shams, Yashar (Faculty of Business Management, 2013)
The present study will examine whether the relationship between HR practices and job performance could be related by the extent to which individuals will inclined to work hard, careful, and goal-oriented. On the basis of the literature, it will be hypothesized that conscientiousness strengthens the relationship between HRM practices and supervisor ratings of task and contextual performance as well as active learning. Researcher will examine hypotheses which are about HR practices has positively related to task performance, contextual performance and active learning, particularly for employees high in conscientiousness. The hypotheses will be tested on a sample of 144 employees from Oil and Gas Industry in Malaysia. Regression analysis will be used as analysis method with SPSS.